Modeling of the substrate cooling system in the installation for the deposition of coatings by the gas plasma method - Martynov, S.O.; Luchaninov, O.A.; Lukyanova, V.P.; Prokhorets, S.I.; Slabospytska, O.O.; Khazhmuradov, M.A. (Problems of Atomic Science and Technology, 2023)
The efficiency of diamond coating synthesis depends on both the parameters of the plasma flow and the uniform temperature distribution on the surface of the substrate on which the coating is synthesized. Mathematical modeling of the substrate cooling system in the installation for the deposition of coatings by the gas plasma method was carried out in order to find optimal parameters at which high density and radial uniformity of energy and chemically active particle flows are simultaneously achieved on the substrate in the process of synthesis of diamond coatings. The task was solved by direct search methods using the FlowSimulation module of the SolidWorks package. Ефективність синтезу алмазного покриття залежить від параметрів плазмового потоку й однорідного розподілу температури на поверхні підложки, на якій здійснюється синтез покриття. Проведено математичне моделювання системи охолодження підложки в установці для осадження покриттів газоплазмовим методом з метою знаходження оптимальних параметрів, при яких як висока щільність, так і радіальна однорідність енергії і хімічно активних потоків частинок одночасно досягаються на підложки в процесі синтезу алмазних покриттів. Завдання вирішувалося методами прямого пошуку із використанням модуля FlowSimulation пакета SolidWorks.